The Origins and Evolution of Consumer Capitalism: The Paradoxes Posed by Continuous Mass Production. Issue 2 (3rd April 2022) - Watkins, John P.
Abstract: Continuous-mass production technology, widely adopted in the late nineteenth, early twentieth centuries, enabled businesses to vastly increase output. Thorstein Veblen was among the first to observe the business response: how to prevent production from exceeding what the market could profitably absorb? How to prevent losses? How to increase profits? Continuous-mass production introduced consumer capitalism, applying the technology to consumer goods, creating the necessity of increasing consumer demand, making imperative adopting the corporate form of business enterprise. Continuous-mass production has accentuated a number of paradoxes, some of which were addressed by Veblen, Polanyi, and Keynes. Those paradoxes include the prospect of depression, the rise of dynastic ambitions channeling the increased output into militarism, financial innovations involving identifying and liquefying consumer assets to provide credit and expand demand, laying the foundation for the financialization of the economy. Financialization culminated in the Great Financial Crisis (GFC), requiring massive government intervention. The GFC gave rise to Modern Monetary theory, overcoming the limits of the market economy. And the environmental crisis resulting from the commodification of everything, accentuated by applying continuous mass production to the extraction and burning of fossil fuels, combined with a belief in infinite growth.